2004
DOI: 10.1007/s00415-004-0476-2
|View full text |Cite
|
Sign up to set email alerts
|

Simulator based rehabilitation in refractory dizziness

Abstract: Both groups improved but exposure to simulator motion gave overall better results. These effects were also observed in psychological symptoms and partly relate to simulator effects on visual vertigo symptoms. Visual motion and visuo-vestibular conflict situations should be incorporated in the rehabilitation of patients with refractory dizziness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
132
1
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(142 citation statements)
references
References 42 publications
(47 reference statements)
5
132
1
4
Order By: Relevance
“…Hemiparetic stoke patients who performed a task-orientated exercise program under conditions of vision and surface manipulations showed more improvement in their standing balance than a control group that performed a conventional task-oriented program [25]. Patients with balance control problems [26][27][28] and gait disturbances [29,30] have also demonstrated improvement following adaptive generalization training. We believe analogous improvements might be made in the reduction of gait ataxia in returning astronauts if they are trained to make rapid adjustments to novel physical and sensory stimuli such as that produced by variations in visual flow and support surface stability.…”
Section: Discussionmentioning
confidence: 99%
“…Hemiparetic stoke patients who performed a task-orientated exercise program under conditions of vision and surface manipulations showed more improvement in their standing balance than a control group that performed a conventional task-oriented program [25]. Patients with balance control problems [26][27][28] and gait disturbances [29,30] have also demonstrated improvement following adaptive generalization training. We believe analogous improvements might be made in the reduction of gait ataxia in returning astronauts if they are trained to make rapid adjustments to novel physical and sensory stimuli such as that produced by variations in visual flow and support surface stability.…”
Section: Discussionmentioning
confidence: 99%
“…After the title and abstract screening, 28 studies were identified as potentially eligible. However, after full text screening, 19 studies were excluded due to the following reasons: sample outside the pre-specified age range (n=14) [8][9][10][11][12][13][14][15][16][17][18][19][20][21] , lack of randomization (n=4) [22][23][24][25] , and sample with no complaints or vestibular disorders (n=1) 26 . Thus, nine randomized controlled trials were eligible for inclusion in this review and had their content critically analyzed.…”
Section: Resultsmentioning
confidence: 99%
“…B. Trainingsprogramme, die verschiedene Balanceaufgaben [19] oder spezielle TaiChi-Übungen [12] verwenden. Bei anderen Methoden befindet sich der Patient in einem Simulator, mit dessen Hilfe Übun-gen in einer virtuellen (visuellen) Realität durchgeführt werden [14,23].…”
Section: Placebokontrollierte Doppelblind-pilot-studie Zur Rehabilitaunclassified